1992
DOI: 10.1128/mcb.12.8.3514
|View full text |Cite
|
Sign up to set email alerts
|

Regulation and expression of a growth arrest-specific gene (gas5) during growth, differentiation, and development.

Abstract: The growth arrest-specific gas5 gene was isolated from mouse genomic DNA and structurally characterized.The transcriptional unit is divided into 12 exons that span around 7 kb. An alternative splicing mechanism gives rise to two mature mRNAs which contain either 11 or 12 exons, and both are found in the cytoplasm of growth-arrested cells. In vivo, the gas5 gene is ubiquitously expressed in mouse tissues during development and adult life. In Friend leukemia and NIH 3T3 cells, the levels of gas5 gene mRNA were h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
166
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 200 publications
(175 citation statements)
references
References 47 publications
9
166
0
Order By: Relevance
“…Sequence analysis of the promoter of Gas5 spanned 1621 nucleotides upstream of the transcription start site. 19 Six singlenucleotide polymorphisms were observed in BXSB, compared to both B10 and B6, which were identical: À1285 (G in B10, A in BXSB), À1122 (T to G), À314 (G to C), À277 (A to C), À267 (A to T) and À258 (G to A). The polymorphism at À267 was predicted to lead to a loss of an Sp1 consensus-binding site.…”
Section: Validation Of Microarray Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Sequence analysis of the promoter of Gas5 spanned 1621 nucleotides upstream of the transcription start site. 19 Six singlenucleotide polymorphisms were observed in BXSB, compared to both B10 and B6, which were identical: À1285 (G in B10, A in BXSB), À1122 (T to G), À314 (G to C), À277 (A to C), À267 (A to T) and À258 (G to A). The polymorphism at À267 was predicted to lead to a loss of an Sp1 consensus-binding site.…”
Section: Validation Of Microarray Resultsmentioning
confidence: 93%
“…While the function of Gas5 remains unclear, it has been suggested that it plays a role in the cellular decision to enter the apoptotic pathway. 19 The potential loss of an Sp1 binding site from the promoter of the BXSB allele of Gas5 may be the cause of the down regulation. Further work is underway to characterise which splenocytic cell population Gas5 is normally expressed in and the functional relevance of the promoter polymorphisms.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, Gas5 was shown to be ubiquitously expressed during mouse development and adult life, and also to be expressed only at low levels in actively growing Friend leukemia and NIH 3T3 cells, with substantially increased abundance in cells grown to saturation density (Coccia et al, 1992). Gas5 RNA levels appeared to be regulated primarily through changes in its rate of degradation rather than through changes in its transcription rate (Coccia et al, 1992;Smith and Steitz, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Because of its speci®c regulation in non dividing NR cells, the QR1 gene represents a useful model to study mechanisms that turn on di erentiation genes and to investigate their regulation when proliferating precursor cells exit from the cell cycle. Thus far, there have been only few reports on the characterization of regulatory sequences that control expression of the so-called growth arrest speci®c genes (Coccia et al, 1992;Mao et al, 1993;Del Sal et al, 1994;Mao et al, 1993). In this study, we have characterized a novel element, the C box, that is able to confer upon homologous and heterologous promoters responsiveness to cell division arrest.…”
Section: Discussionmentioning
confidence: 99%
“…A particular group of genes called GAS (for Growth Arrest Speci®c) genes, were functionally de®ned as being induced in growth arrested ®broblasts and arose as models for studying the mechanisms and signaling pathways involved in this process (Barone et al, 1994;Del Sal et al, 1992;Schneider et al, 1988). The GAS family includes both ubiquitous genes (Coccia et al, 1992) and di erentiation markers (Fabbretti et al, 1995). Various functions have been attributed to these genes and linked either to growth suppression (Del Sal et al, 1992, 1994, apoptosis and, surprisingly, growth promotion (Goruppi et al, 1996;Lih et al, 1996).…”
Section: Introductionmentioning
confidence: 99%